Market versus Residence Principle: Experimental Evidence on the Effects of a Financial Transaction Tax. (24th October 2017) - Huber, Jürgen; Kirchler, Michael; Kleinlercher, Daniel; Sutter, Matthias
Abstract : The effects of a financial transaction tax (FTT) are scientifically disputed, as seemingly small details of its implementation may matter a lot. In this article, we provide experimental evidence on the different effects of an FTT, depending on whether it is implemented as a tax on markets, on residents, or a combination of both. We find that a tax on markets has negative effects on volatility and trading volume, whereas a tax on residents shows none of these undesired effects. Additionally, we observe that individual risk attitude is not related to traders' reaction to the different forms of an FTT.